Genetic variability and diversity analysis in wheat (Triticum spp.) genotypes using multivariate techniques - SHARMA, SUSHMA; SINGH, VIKRAM; MOR, VIRENDER SINGH; PUNIA, RAMESH CHANDER; HEMENDER, HEMENDER; YASHVEER, SHIKHA; KHAN, MUJAHID; SANGWAN, SONALI (The Indian Journal of Agricultural Sciences, 2021)
Thirty-four Indian wheat (Triticum spp.) varieties released from 1933 to 2010 were evaluated at CCS Haryana Agricultural University, Hisar (India) for genetic variability and diversity based on their morphological and seed vigour parameters during 2015-16. Significant variations were exhibited by the genotypes for all 26 traits under study. Awn length and dehydrogenase activity had maximum values of genotypic coefficient of variation (GCV), phenotypic coefficient of variation (PCV), heritability and genetic advance as percentage of mean for morphological and seed vigour traits, respectively. In the principal-component analysis of morphological traits, first five principal components accounted for about 77.56% of the total variation. Whereas, first three principal components explained about 84.19% of the total variation for seed vigour parameters. Principal-component analysis score identified variety WH 1105 as most vigorous variety as well potential genotype for morphological traits.